Answer:
f(x) is an odd function and g(x) is an even function
Step-by-step explanation:
Even Function :
A function f(x) is said to be an even function if
f(-x) = f(x) for every value of x
Odd Function :
A Function is said to be an odd function if
f(-x)= -f(x)
Part a)
[tex]f(x)=x^3+x[/tex]
let us substitute x with -x
[tex]f(-x) = (-x)^3-x\\=-x \times -x \times -x\\=-x^3-x\\=-(x^3+x)\\=-f(x)[/tex]
Hence
f(-x)=-f(x)
There fore f(x) is an odd function
[tex]g(x)=x^2+1[/tex]
Substituting x with -x we get
[tex]g(-x)=(-x)^2+1\\=-x \times -x+1\\=x^2+1\\=g(x)[/tex]
Hence g(-x)=g(x)
Therefore g(x) is an even Function.
Part b)
hf(x)=hx^3